EU-NATO Cooperation Financing and Relation to Europe’s Socio-economic Model - Kaid, Amira; Hnát, Pavel, 1981-; Antal, Jarolím, 1986-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
Given the recently signed EU-NATO declaration the objective of which was to strengthen EU-NATO cooperation, this thesis aims to look more closely at the defense spending and NATO contributions in the European Union. This was done by first analyzing the European Union’s financial framework, determining how much is spent on defense relative to other sectors and describing NATO’s funding scheme. The European Union countries were then divided into five models (Nordic, Liberal, Continental, Southern and post-Communist) and then data on the direct and indirect NATO contributions was used to compare the defense spending of the different models. The results showed that there were disparities even among the countries within the individual models, but there were some observable patterns in the data. In terms of direct contributions, the Southern model countries tended to spend more on military personnel while the post-Communist countries spent more on military equipment and infrastructure. The indirect contribution goals of dedicating 2% of GDP to defense and 20% of overall defense expenditures to major equipment, were met by just a few of the countries (Greece, Latvia, Britain). The case study looked at the military expenditures of Greece, Britain, France and Germany from 1970-2017 to determine some of the factors that might have led to the countries’ ability to meet NATO’s 2% goal. It was found that Greece’s strained relationship with Turkey and the migrant crises were major factors that lead to higher military spending. For Britain it was its central role in the Cold War in pushing back against the Soviets. For France the first oil shock and Chirac’s defense spending reforms that lead to a decrease in defense spending. Finally, Germany’s unification and the subsequent anti-war attitudes that arose there have caused them to decrease their defense spending significantly throughout the years.
It was shown defense spending in Europe is not declining that given the recent agreements surrounding the EU-NATO declaration that European defense spending is expected to increase in the near future.
Vedoucí práce: Pavel Hnát
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses